(Re)Thinking children as fully (in)human and literacies as otherwise through (re)etymologizing intervene and inequality. (March 2020) - Kuby, Candace R; Rucker, Tara Gutshall
In response to the guest editors' call to attend to literacy and language as bodily practices and to (re)think social inequality in young children's literacies, we read a couple of publications by Rosi Braidotti, Maggie MacLure, Nathan Snaza, Sarah Truman and Karin Murris (and others) in relation to a personal narrative gameboard coming to be in a second-grade Writers' Studio. We also engage in (re)etymologizing the words intervene and inequality. (Re)etymologizing is an enquiry practice of searching for the meanings and origins of words not in an effort to know the words, find their true meaning(s), or to nail-down the definitions, but rather in an effort to unmake the words and think differently. Through these musings, writings and thinkings, we explore the question posed by the guest editors: How can we think literacy otherwise? In doing so, we offer invitations and questions for the reader to ponder related to the ethics and justice orientation of poststructural and posthumanist theories and what they have to offer early childhood literacies.